Side effects reported by European consumers for medications for erectile dysfunction - Lise Aagaard; Ebba Holme Hansen (Wolters Kluwer Medknow Publications, 2013)
Objective: To characterise consumer adverse drug reaction (ADR) reports for phosphodiesterase type 5 (PDE5) inhibitors. Methods: We included ADR reports submitted by adults to the European ADR database (EudraVigialnce) from 2007 to 2011. ADRs were classified according to type, seriousness and age and sex of consumers. The unit of analysis was one ADR. Findings: Totally, 328 ADRs were reported for sildenafil and vardenafil, and only 5% of these were serious. The largest number of reported ADRs was found for sildenafil, i.e., "lack of efficacy" and/or "drug efficacy decreased" ( n = 134) and "headache" ( n = 21). Conclusion: ADRs reported by consumers for PDE5 inhibitors were relatively low, and only few ADRs were serious.